Analisis Kebutuhan dan Perancangan Antarmuka Sistem Informasi Peminjaman Mobil Dinas dan Risalah Lelang pada KPKNL Palembang - Gusmelia Testiana; Dinda Ayu Ristiantin; Aulia Berliana Shanti; Mesya Uswatun Hasanah; Awang Pramana Oka Rio; Yoniza Rahmawati (GLOBAL SCIENTS PUBLISHER, 2026)
The development of information technology encourages government agencies to improve the effectiveness of data management and administrative services through the utilization of information systems. The Palembang State Asset and Auction Service Office (KPKNL Palembang) still faces several challenges in managing official vehicle borrowing and auction minutes because some administrative processes are carried out manually. This condition has the potential to cause delays in data retrieval, recording errors, and difficulties in monitoring borrowing status. This study aims to analyze user requirements and design the interface of an Information System for Official Vehicle Borrowing and Auction Minutes that meets the operational needs of KPKNL Palembang. Data collection methods were carried out through observation, interviews, and documentation. The results indicate that the designed system requires features for vehicle data management, auction minutes data, borrowing requests, borrowing approvals, returns, data searches, and reporting. The interface design was developed based on user requirements to provide a system overview that is easier to use, structured, and supports the effectiveness of administrative management. With this design, the future system development process is expected to be carried out in a more directed manner according to user needs.